Interventions at a Quotidian Scale. Chocolate Shop in West Santiago [Intervenciones a Escala Cotidiana. Chocolatería en Santiago Poniente] - Alvarez-Gutierrez, P (Universidad Austral de Chile, 2016)
At present, do-it-yourself housing expansions are entropic features of Santiago s urban landscape. Such living spaces/compartments prevail in the larger areas of the consolidated peripheral territory. Their development is totally decoupled from effective urban planning tools. This architectural exercise faces the endeavors of this urban phenomenon proposing-through design-the cooperation between architects and users, who take part early on in the project s process and then, in the construction, jointly address housing spatial modification demands.